Samsung Galaxy Tab S for dummies - Gookin, Dan (--For dummies., 2015)
Provides a basic introduction to the latest version of the Samsung tablet computer, covering topics such as initial set-up, browsing the web, using social media, syncing data with a desktop, texting, and navigating with Google Maps.